2014
DOI: 10.5935/1678-9741.20140052
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fractal dimension and Shannon entropy in myocytes from rats treated with histidine-tryptophan-glutamate and histidine-tryptophan cetoglutarate.

Abstract: IntroductionSolutions that cause elective cardiac arrest are constantly evolving, but the ideal compound has not yet been found. The authors compare a new cardioplegic solution with histidine-tryptophan-glutamate (Group 2) and other one with histidine-tryptophan-cetoglutarate (Group 1) in a model of isolated rat heart.ObjectiveTo quantify the fractal dimension and Shannon entropy in rat myocytes subjected to cardioplegia solution using histidine-tryptophan with glutamate in an experimental model, considering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
8
0
3
Order By: Relevance
“…Another interesting aspect would be the analysis of variations of the HTK solution. A Brazilian study, published in 2014, found no difference between the original composition and another one with glutamate replacing ketoglutarate in an experimental model with rats [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting aspect would be the analysis of variations of the HTK solution. A Brazilian study, published in 2014, found no difference between the original composition and another one with glutamate replacing ketoglutarate in an experimental model with rats [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Outro estudo 25 observou em seus estudos a eficácia da utilização da DF para verificar alterações morfológicas sobre o tecido muscular cardíaco de ratos. O miocárdio ventricular pode adaptar-se a estresses sofridos em sua estrutura, conservando sua inicialmente sua dimensão fractal.…”
Section: Discussionunclassified
“…Many authors have discussed the effects of the different types of cardioplegia [ 9 - 11 ] . Antegrade and/or retrograde delivery of cardioplegia has also been a matter of constant debate [ 12 - 14 ] .…”
Section: Discussionmentioning
confidence: 99%